2011
DOI: 10.1371/journal.pone.0016945
|View full text |Cite
|
Sign up to set email alerts
|

A Hepatic Protein, Fetuin-A, Occupies a Protective Role in Lethal Systemic Inflammation

Abstract: BackgroundA liver-derived protein, fetuin-A, was first purified from calf fetal serum in 1944, but its potential role in lethal systemic inflammation was previously unknown. This study aims to delineate the molecular mechanisms underlying the regulation of hepatic fetuin-A expression during lethal systemic inflammation (LSI), and investigated whether alterations of fetuin-A levels affect animal survival, and influence systemic accumulation of a late mediator, HMGB1.Methods and FindingsLSI was induced by endoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
0
15

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(156 citation statements)
references
References 56 publications
7
134
0
15
Order By: Relevance
“…4C). We also observed that upon bacterial infection of macrophages in vitro, there was a noticeable accumulation of HMGB1 in the cytosol, which also occurs upon LPS stimulation (36,37) (Fig. 4D).…”
Section: Resultsmentioning
confidence: 52%
“…4C). We also observed that upon bacterial infection of macrophages in vitro, there was a noticeable accumulation of HMGB1 in the cytosol, which also occurs upon LPS stimulation (36,37) (Fig. 4D).…”
Section: Resultsmentioning
confidence: 52%
“…RAW 264.7 macrophages, U937 monocytes and primary macrophages were cultured in DMEM supplemented with 1% penicillin/streptomycin and 10% FBS. Adherent macrophages or monocytes were gently washed with, and cultured in, DMEM before stimulating with LPS (0.5 μg/mL), HMGB1 (0.5 μg/mL) or human SAA, in the absence or presence of PKR inhibitors or SAA-neutralizing IgGs for 16 h. Subsequently, the cell-conditioned culture media were analyzed respectively for levels of HMGB1, nitric oxide and other cytokines by Western blotting analysis, the Griess reaction and cytokine antibodies arrays as previously described (38,39).…”
Section: Cell Culturementioning
confidence: 99%
“…To evaluate the role of SAA in lethal sepsis, Balb/C mice (male, 7-8 wks, 20-25 g) were subjected to lethal endotoxemia or sepsis induced by cecal ligation and puncture (CLP) as previously described (38,39,42). Briefly, the cecum of Balb/C mice was ligated at 5.0 mm from the cecal tip and then punctured once with a 22-gauge needle.…”
Section: Animal Models Of Endotoxemia and Polymicrobial Sepsismentioning
confidence: 99%
“…Both RAW 264.7 cells and primary macrophages were cultured in DMEM supplemented with 1% penicillin/streptomycin and 10% FBS. Adherent macrophages were gently washed with, and cultured in, DMEM before stimulating with LPS (0.5 μg/mL) in the absence or presence of CBX or purinergic P2X 7 R antagonists (oATP, 50 μmol/L; BBG, 0.5 μmol/L; KN62, 0.5 μmol/L) for 16 h. Subsequently, the cell-conditioned culture media were analyzed for levels of HMGB1, nitric oxide (NO) and other cytokines by Western blotting analysis, the Griess reaction, ELISA, and cytokine antibodies arrays as described previously (36)(37)(38).…”
Section: Cell Culturementioning
confidence: 99%